Brain Stem and Entire Spinal Leptomeningeal Dissemination of Supratentorial Glioblastoma Multiforme in a Patient during Postoperative Radiochemotherapy. Issue 24 (June 2015) - Kong, Xiangyi; Wang, Yu; Liu, Shuai; Chen, Keyin; Zhou, Qiangyi; Yan, Chengrui; He, Huayu; Gao, Jun; Guan, Jian; Yang, Yi; Li, Yongning; Xing, Bing; et al.
<x xml:space="preserve">Abstract</x> Abstract Glioblastoma multiforme (GBM) is the most common primary malignancy of the central nervous system in adults. Macroscopically evident and symptomatic spinal metastases occur rarely. Autopsy series suggest that approximately 25% of patients with intracranial GBM have evidence of spinal subarachnoid seeding, although the exact incidence is not known as postmortem examination of the spine is not routinely performed.1–3 Herein, we present a rare case of symptomatic brain stem and entire spinal dissemination of GBM in a 36-year-old patient during postoperative adjuvant radiochemotherapy with temozolomide and cisplatin. Visual deterioration, intractable stomachache, and limb paralysis were the main clinical features. The results of cytological and immunohistochemical tests on the cerebrospinal fluid cells were highly suggestive of spinal leptomeningeal dissemination. After 1 month, the patient's overall condition deteriorated and succumbed to his disease. To the best of our knowledge, this is the first reported case of GBM dissemination presenting in this manner. Because GBM extracranial dissemination is rare, we also reviewed pertinent literature regarding this uncommon entity. Although metastases to spinal cord from GBM are uncommon, it is always important to have in mind when patients with a history of GBM present with symptoms that do not correlate with the primary disease pattern.